The Legal Policies Based Ecoregion Waste Handling in the Bengawan Solo River - Absori Absori; Valisher Sapayev; Endah Pujiastuti; Mohammad Indra Bangsawan; Trias Hernanda (Unissula, 2025)
The decrease in Bengawan Solo River’s water quality threatens the livelihood of the people living around this river, considering that it is one of the sources of their livelihood. There has been large-scale pollution in the upstream area of Bengawan Solo River caused by alcohol waste, carcasses of pig cattle, and wastewater from textile factories that were not processed in the wastewater processing installation. The aim of this research is to analyze how the ecoregion methods can be applied and how it kan became solution in managing the Bengawan Solo River to free from the threat of waste pollution.. Methods: This research employed the sociological method, where the authors collected field data from seven districts or regencies. The primary data were sourced from observation and interviews, while the secondary data consisted of regulations, laws, etc. These data were descriptively analyzed to illustrate policies for handling waste. Waste processing issues happen in almost every area in Indonesia. Findings: Even though legal instruments that govern this issue already exist, such an issue cannot be resolved through the regulations of one city or regency. Thus, there is a need for inter-regency regulations. There needs to be a new concept to help protect this river, which is the ecoregion approach.